Mathematical Communication Skills of Female Students in Solving Derivative Problems - Ratna Dwi Oktavia; Rita Lefrida; Alfisyahra Alfisyahra; Pathuddin Pathuddin (IKIP Mataram, 2024)
This study aimed to examine the mathematical communication skills of female students in solving derivative problems in the eleventh grade at SMA Negeri 1 Sigi. The research followed a qualitative approach with a descriptive design. The study sample consisted of three female students selected based on a questionnaire focusing on feminine gender traits. Data were collected through written tests, interviews, and direct observation of the subjects. The dependability and credibility techniques were used to ensure the quality of the research findings. Data analysis involved three stages: data condensation, data presentation, and drawing conclusions. This study contributes to the existing literature by addressing the gap in understanding the mathematical communication skills of students with feminine gender traits, specifically in the context of solving derivative problems. The uniqueness of this study lies in the use of a feminine questionnaire for subject selection and the integration of mathematical language with everyday language and physical gestures in the evaluation of mathematical ideas. The findings revealed that female students with feminine gender traits demonstrated proficiency in all indicators of mathematical communication skills, including: (1) the ability to communicate their mathematical thoughts coherently and clearly to their peers and teachers; (2) effective use of mathematical language, such as numbers, letters, symbols, charts, graphs, and logical connections, in conjunction with everyday language and physical gestures when presenting, solving, and evaluating mathematical ideas during interactions with others; and (3) the capacity to explain mathematical ideas, situations, or relationships in written form. These results suggest that approaches combining mathematical language with physical interaction and everyday language can enhance the effectiveness of mathematical communication. The findings of this research can be utilized as a foundation for developing more inclusive and adaptive teaching strategies that consider gender differences in mathematics education.